Interelasi kecerdasan sosial dengan interaksi sosial mahasiswa luar Jawa Fakultas Ilmu Sosial Universitas Negeri Malang - Mochamad Ilham Akbar; Tasya Kartika Chandra; Riska Ayu Setyowati; Faizah Isnaeni; Safira Lailatuz Zahro; Ananda Dwitha Yuniar (Universitas Negeri Malang, 2021)
Social intelligence is an individual's ability to take action and mindset in living life as a social being. Social intelligence is used by individuals to interact and understand other individuals, phenomena or the environment around them. This social intelligence consists of basic empathy, listening, empathic accuracy, and social understanding or cognition. Meanwhile, this social facility consists of synchrony, self-presentation, influence, and care. At this time in the world of academia, it focuses more on critical thinking which tends to lead to intellectual intelligence. Social intelligence is very important for students in the world of academia and for their adjustment to the social environment which is useful as a support for social life. It is important for a student to have social intelligence so that his life is balanced between his intellectual and social abilities. Because with social intelligence, students will find it easier to build good relationships with the community. the importance of social intelligence for students needs to be studied in academia at this time. To study this, the researcher examined the interrelation of social intelligence with the social interaction of students outside Java at the Faculty of Social Sciences, State University of Malang. The research method used was a qualitative method with a descriptive approach. The data collection techniques used were observation and interviews. Kecerdasan sosial merupakan kemampuan individu dalam melakukan tindakan dan pola pikir dalam menjalani kehidupan sebagai makhluk sosial. Kecerdasan sosial digunakan oleh individu untuk berinteraksi dan memahami individu lain, fenomena atau lingkungan disekitarnya. Kecerdasan sosial ini terdiri dari empati dasar, mendengarkan, ketepatan empatik, dan pengertian atau kognisi sosial. Sedangkan fasilitas sosial ini terdiri dari sinkroni, presentasi diri, pengaruh, dan kepedulian. Pada saat ini dalam dunia akademisi lebih menitik beratkan pada pemikiran kritis yang cenderung mengarah pada kecerdasan intelektual. Kecerdasan sosial sangat penting bagi mahasiswa dalam dunia akademisi dan untuk penyesuaian diri terhadap lingkungan sosial yang berguna sebagai penunjang kehidupan bermasyarakat. Kecerdasan sosial penting dimiliki oleh seorang mahasiswa agar kehidupannya seimbang antara kemampuan intelektual dan sosialnya. Karena dengan adanya kecerdasan sosial maka mahasiswa akan lebih mudah membangun hubungan yang baik dengan masyarakat. pentingnya kecerdasan sosial bagi mahasiswa ini perlu untuk dikaji dalam dunia akademisi pada saat ini. Untuk mengkaji hal ini, peneliti mengkaji interelasi kecerdasan sosial terhadap interaksi sosial mahasiswa luar jawa di Fakultas Ilmu Sosial Universitas Negeri Malang dengan metode penelitian yang peneliti gunakan adalah metode kualitatif dengan pendekatan deskriptif dengan teknik observasi dan wawancara sebagai teknik pengumpulan data.